The Effect of Value-Added Tax Policy on Per Capita Income and Inequality in Indonesia - Sekar Ayu Cahyaning Asri; Deky Aji Suseno (Universitas Hayam Wuruk Perbanas, 2023)
The implementation of value-added tax (VAT) policy holds significant sway over state revenue. This study delves into the impact of value-added tax on economic growth and inequality within Indonesia. Panel data spanning from 2017 to 2021, encompassing 34 provinces, was scrutinized using the panel vector error correction model alongside the Sobel test. The study's findings reveal that while VAT directly affects per capita income, it exerts no discernible influence on inequality, either directly or indirectly. When subjected to the PVECM test, VAT shows no long-term impact on income. In contrast, domestic investment and the democracy index exhibit a positive and noteworthy effect on income levels. Notably, VAT and foreign investment do not demonstrably impact inequality. In the long run, it is per capita income, the democracy index, and domestic investment that bear influence. In the short term, however, none of these variables significantly affect inequality. It is worth mentioning that per capita income experiences a positive and substantial influence from the democracy index and domestic investment. This research furnishes policymakers with valuable insights to guide revenue management and allocation, thereby advancing economic development and addressing prevailing social challenges.